1994
DOI: 10.1063/1.466909
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the ground vibrational state structure of H35Cl trimer based on the resolved K, J substructure of the ν5 vibrational band

Abstract: Investigation of an H-bonded dimer: Calculations of bonding structures and temperature dependence of the librational substructure of the OH-stretching band Dipole moment analysis of excited van der Waals vibrational states of ArH35ClThe high resolution rovibrational IR spectrum of the antisymmetric H 35 CI stretching lI5 vibrational band in the (H 35 Clh isotopomer of the trimer has been measured with a tunable infrared diode laser supersonic jet spectrometer. One of the most prominent features of the spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…The most intense peak in the spectrum at 2807.7 cm -1 is assigned to the cyclic trimer based on the pick-up cell pressure dependence experiments (see Figure S3 in the Supporting Information). It is also in good agreement with results of previous experiments in the gas phase, 5,9,10,32,33 which are listed in Table 1. Similarly, the strong peak at 2772.3 cm -1 is assigned to the cyclic tetramers.…”
Section: Spectra Of (Hcl) N In He Dropletssupporting
confidence: 93%
“…The most intense peak in the spectrum at 2807.7 cm -1 is assigned to the cyclic trimer based on the pick-up cell pressure dependence experiments (see Figure S3 in the Supporting Information). It is also in good agreement with results of previous experiments in the gas phase, 5,9,10,32,33 which are listed in Table 1. Similarly, the strong peak at 2772.3 cm -1 is assigned to the cyclic tetramers.…”
Section: Spectra Of (Hcl) N In He Dropletssupporting
confidence: 93%
“…The first high resolution (HR) spectra of these hydrogen bonded complexes enabled access to the dimer structure, dissociation energy, predissociation lifetimes and tunneling dynamics, and ultimately permitted us to build reliable intermolecular potential energy surfaces for such four-atom clusters. 4,49,50 In contrast to the large number of hydrogen bonded dimer studies reported up to now, only a few homomolecular trimers such as (HCCH) 3 , 51 (HCN) 3 , 52 (HF) 3 , 9,36 (HCl) 3 , 53 (CO 2 ) 3 , 54,55 (DF) 3 , 41 and (H 2 O) 3 56 have been studied in nearly isolated gas phase supersonic jet environments associated with near or far infrared (FIR) tunable laser spectroscopy. Apart from (HF) 3 , molecular constants could be obtained from rotationally resolved vibrational spectra.…”
Section: Introductionmentioning
confidence: 97%
“…The donor stretching modes recorded for (HCl) 3 and (DF) 3 have pointed out the problems related to the analysis of higher energy bands: depending on the high density of levels and the strength of the coupling with the bath of states via intramolecular vibrational redistribution (IVR) a loss of fully resolved structure due to significant lifetime homogeneous broadening is likely to be observed, which is indeed large for (DF) 3 (4 GHz) 41 but much smaller for (HCl) 3 (r90 MHz). 53 Nevertheless, spectral analysis from such experiments provided reliable information about the structure and dynamics of trimers. This is not the case of the hydrogen fluoride trimer and larger clusters for which available experimental IR data beyond cryogenic matrix spectra are very scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This spectrometer involved the use of lead salt tunable diode lasers in the range of 3-5 lm and took advantage of comparable wavelength modulation to achieve a minimum detectable absorption of 3 · 10 À5 . Various molecular complexes have been investigated using this spectrometer [25][26][27][28][29][30][31][32][33], and have yielded excellent results for a range of intramolecular vibrations in molecular complexes, but usually inadequate sensitivity was available for generation of the necessary data for low frequency intermolecular rovibrational parameters for these weakly bound species. In order to overcome such limitations, we now report the development of a diode laser spectrometer that incorporates the ultrasensitive high frequency wavelength modulation static gas phase methods [34][35][36] for operation in cw supersonic jet expansions.…”
Section: Introductionmentioning
confidence: 98%